Hydrophobins and chaplins: Novel bio-surfactants for food dispersions a review. (May 2021) - Dokouhaki, Mina; Hung, Andrew; Kasapis, Stefan; Gras, Sally L.
Abstract: Background: Food colloid stability is critical to many food properties and surfactants that can provide long-term stability against phase separation are highly desirable. The hydrophobins and the chaplins are proteins secreted by filamentous microorganisms that spontaneously self-assemble into amphipathic layers at a hydrophilic-hydrophobic interface providing surface activity. These proteins have great potential as biosurfactants or foaming agents in food products and other dispersed systems. Scope and approach: This review seeks to provide a better understanding of the common structural features of the hydrophobin and chaplin proteins and their functional properties, including surface activity, which arise from these structural features. The ability of these two protein classes to assemble at the interface and stabilize dispersed systems is compared. The mechanism of protein self-assembly at the interface, role of cysteine residues in self-assembly and the formation of fibrils are also explored. Potential methods and challenges in the production of these proteins for commercial applications are reviewed, together with new promising areas of research. Key findings and conclusions: The hydrophobins and chaplins display a surface activity comparable to traditional surfactants and form interfacial films with highly favourable rheological properties. Proteins from these two groups of naturally derived molecules have the potential to stabilize food or pharmaceutical dispersions against coalescence and disproportionation over a wide range of pH for lengthy periods of time (up to 45 days). While there is a significant promise for their use in the stabilization of dispersed systems, further optimization of protein production yield will be required for commercial applications. Highlights: Interfacial films of hydrophobins or chaplins have exceptional elasticity. These protein films are as thick as those formed by traditional surfactants. The dispersions formed by hydrophobins and chaplins are also highly stable. The chaplin films possess distinct pH-dependent interfacial properties. The self-assembly of hydrophobins at the interface is insensitive to pH.